Freudianism in the discourse of George Tarabishi from modernity to civilizational backwardness (An Approach in the Light of the Traveling Theory) - عبد الرحمن محمد نعسان ,; لطفيَّة إبراهيم برهم,; زكوان جمعة العبدو , (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research is based on the assumption that: the transition of a theory from one civilizational context to another requires cognitive shifts. Taking the traveling theory of (Edward Said) as a method, and from the discourse of (Sigmund Freud) and (George Tarabishi) as a subject. The research seeks to answer the questions: Does the transition of a theory from a social historical context to a different context give the theory an enriching development, or does it distort the theory and make it lose its effectiveness? Does this transition make the second theory dependent on the first? What is the impact of historical and cultural contexts on cognitive variables? In the light of these questions, The research represents the discourses of Freud and Tarabishi, taking into account the following methodological steps: Understanding of social historical contexts. Analyze the reference context conceptually and applied. Showing the cognitive changes that Tarabishi made to Freud's discourse, then evaluating their effectiveness and purpose.